PENINGKATAN KETERAMPILAN MANAJERIAL SISWA MELALUI PENDAMPINGAN TATA KELOLA BANK SAMPAH BERKELANJUTAN - Zalikha Zalikha; Fazil Fazil; Ekamaida Ekamaida (Jurnal AbdiMas Nusa Mandiri, 2026)
This community service program aimed to improve students’ managerial skills through mentoring in sustainable waste bank management at SMP Negeri 1 Peureulak. The program involved 34 students who initially had limited understanding of organizational management and simple administration in waste handling. The methods included socialization, structured training, hands-on practice, and continuous mentoring using a participatory approach. The implementation stages consisted of needs assessment, basic management training, operational practice of waste bank activities, and monitoring and evaluation. The results showed an improvement in students’ managerial skills, as indicated by an increase in the average score from 64 to 88, equivalent to 24 points or 37.5% compared with the initial score. In addition, 29 of 34 students, or 85.3%, met the criteria for independent performance by completing at least four of five practical indicators without direct assistance from the mentoring team. These indicators included waste sorting, waste classification, transaction recording, task implementation according to assigned roles, and preparation of simple reports. The findings indicate improvement not only in students’ understanding but also in their practical competencies through experiential learning. The program also contributed to the establishment of a more structured waste management system at the school. Therefore, continuous mentoring combined with practice-based learning showed positive results in strengthening students’ managerial skills and environmental responsibility.